Mandibular stability using sliding or conventional four-hole plates for fixation after bilateral sagittal split ramus osteotomy for mandibular setback. Issue 4 (May 2017) - Lee, H.G.; Agpoon, K.J.; Besana, A.N.; Lim, H.K.; Jang, H.S.; Lee, E.S.
Abstract: Our aim was to compare the postoperative stability of the mandible when two different fixation methods had been used after bilateral sagittal split ramus osteotomy (BSSRO) for mandibular setback. The study included 23 patients who had two-jaw BSSRO mandibular setback at the Department of Oromaxillofacial Surgery, Korea University Guro Hospital, between January 2011 and June 2014. The first group (four-hole (control) group, n = 13) comprised patients whose bony segments were fixed with conventional four-hole plates, and the second (sliding plate (experimental) group, n = 10) included patients whose bone segments were fixed with sliding plates. Lateral cephalograms were taken and analysed at three time points: preoperatively (T1), and one week (T2), and 1 year (T3) postoperatively. The Mann–Whitney U test was used to compare the postoperative stability of the mandible in each group. There were no significant differences between the two groups in changes in the horizontal and vertical positions of point B and pogonion postoperatively, nor were there any significant differences between them in ramal inclination and inclination of the SN plane with point B at the given time points (p = >0.05 in surgical changes in the mandible immediately after surgery and 0.397, 0.616, 0.082, 0.951, 0.901, 0.476 in postoperative changes in the mandible 1 week to 1 year after surgery). Like the conventional four-hole plate, the sliding plate can also be used to achieve stability in the fixation of mandibular bone segments after BSSRO.